Estudio de factibilidad para la creación de una microempresa de aperitivos en snack, elaborados con productos del sector para los vendedores informales parroquia San Carlos. Año 2015. - Llanos Villares, Ana Fabiola (2015)
This feasibility study is aimed to create a micro snacks at snack, made with products of the sector to the informal vendors parish San Carlos, processed products made from bananas, ripe and cassava and aimed at people of different ages. For some types of project implementation, methods and research techniques, and used to identify the target population of this study, which was identified 10644 inhabitants. Market analysis allowed us to determine the potential demand for the product is 91% and the effective demand, which is equal to units to meet the needs. On the technical study the optimal size and location of the plant, which will ensure good production results during the first year the company will work to 10% capacity and will produce 125467 units, which will increase year over year was defined. Likewise, the technology needed for the production process of the plant was identified. The organizational structure of the company defined areas according to the hierarchical levels that enables performance with responsibility and efficiency that the company requires. The economic study - financial allowed to know the total amount of investment, amounting to $ 12,918.00 in the financial assessment is determined or NPV of $ 18.825,44 and an IRR of 63%.And a relation I benefit cost of $1.89. Indicators that demonstrate the financial viability d investment. Conclusions and recommendations are more relevant then point out, to finally include the literature. Passwords: Feasibility study Microcompany Products in snack Unreliable salespeople